The factors associated with the burnout syndrome and fatigue in Cypriot nurses: a census report - Raftopoulos Vasilios; Charalambous Andreas; Talias Michael (BMC Public Health, 2012)
Abstract Background Fatigue and burnout are two concepts often linked in the literature. However, regardless of their commonalities they should be approached as distinct concepts. The current and ever-growing reforms regarding the delivery of nursing care in Cyprus, stress for the development of ways to prevent burnout and effectively manage fatigue that can result from working in stressful clinical environments. Methods To explore the factors associated with the burnout syndrome in Cypriot nurses working in various clinical departments. A random sampling method taking into account geographical location, specialty and type of employment has been used. Results A total of 1,482 nurses (80.4% were females) working both in the private and public sectors completed and returned an anonymous questionnaire that included several aspects related to burnout; the MBI scale, questions related to occupational stress, and questions pertaining to self reported fatigue. Two-thirds (65.1%) of the nurses believed that their job is stressful with the majority reporting their job as stressful being female nurses (67.7%). Twelve point eight percent of the nurses met Maslach’s criteria for burnout. The prevalence of fatigue in nurses was found 91.9%. The prevalence of fatigue was higher in females (93%) than in males (87.5%) (p = 0.003). As opposed to the burnout prevalence, fatigue prevalence did not differ among the nursing departments (p = 0.166) and among nurses with a different marital status (p = 0.553). Burnout can be associated adequately knowing if nurses find their job stressful, their age, the level of emotional exhaustion and depersonalization. It has been shown that the fatigue may be thought of as a predictor of burnout, but its influence is already accounted by emotional exhaustion and depersonalization. Conclusion The clinical settings in Cyprus appear as stress generating environment for nurses. Nurses working both in the private and public sector appear to experience low to severe burnout. Self-reported fatigue interferes to the onset of emotional exhaustion and depersonalization.